DEVELOPMENT OF SUSTAINED RELEASE ALOGLIPTIN TABLETS USING A MULTIPARTICULATES SYSTEM MADE OF BENTONITE - KAOUD, RASHAD M.; KHALAF, ALHAMZA HOSHI; ALKRAD, JAMAL ALYOUSSEF (International Journal of Applied Pharmaceutics, 2021)
Objective: This study was designed to evaluate the use of bentonite in the formulation of sustained-release tablets containing alogliptin benzoate after granulation. Methods: Bentonite was used for preparing tablets after granulation. The prepared tablets were tested for their pharmacopeial requirements. Further, a high-performance liquid chromatography (HPLC) method was developed to assess the release pattern of alogliptin from the tablets. Besides, differential scanning calorimetry (DSC), fourier transform infrared spectroscopy (FTIR), and powder X-ray diffraction (XRD) were used for evaluating the compatibility the drugs and bentonite. Finally, the release from the tablets was tested using the paddle apparatus. Results: The FTIR and DSC did not show any interaction between the drug and the excipient in contrast to the powder-XRD pattern, which showed a shift for montmorillonite crystal peak. This shift was interpreted by increasing in the spacing of the crystalline structure of montmorillonite. However, the results of pharmacopeial tests showed that the prepared tablets comply with the compendial requirements, In addition, the release profiles of these tablets with aid of hydroxypropyl methylcellulose (HPMC) as a binder revealed a sustained release of alogliptin. Furthermore, the fitting of release data showed that the release from these tablets followed Fickian diffusion that alogliptin released by diffusion from bentonite gel matrix. Conclusion: Bentonite was successfully used for producing sustained-release tablets of alogliptin. However, maintaining the crystal structure of montmorillonite was essential for building the gel structure of bentonite and releasing the drug in a controlled manner.